Can reductions in water residence time be used to disrupt seasonal stratification and control internal loading in a eutrophic monomictic lake?. (15th February 2022) - Olsson, Freya; Mackay, Eleanor B.; Barker, Phil; Davies, Sian; Hall, Ruth; Spears, Bryan; Exley, Giles; Thackeray, Stephen J.; Jones, Ian D.
Abstract: Anthropogenic eutrophication caused by excess loading of nutrients, especially phosphorus (P), from catchments is a major cause of lake water quality degradation. The release of P from bed sediments to the water column, termed internal loading, can exceed catchment P load in eutrophic lakes, especially those that stratify during warm summer periods. Managing internal P loading is challenging, and although a range of approaches have been implemented, long-term success is often limited, requiring lake-specific solutions. Here, we assess the manipulation of lake residence time to inhibit internal loading in Elterwater, a shallow stratifying lake in the English Lake District, UK. Since 2016, additional inflowing water has been diverted into the inner basin of Elterwater to reduce its water residence time, with the intention of limiting the length of the stratified period and reducing internal loading. Combining eight years of field data in a Before-After-Control-Impact study with process-based hydrodynamic modelling enabled the quantification of the residence time intervention effects on stratification length, water column stability, and concentrations of chlorophyll a and P. Annual water residence time was reduced during the study period by around 40% (4.9 days). Despite this change, the lake continued to stratify and developed hypolimnetic anoxia. As a result, there was little significant change in phosphorus (as total or soluble reactive phosphorus) or chlorophyll a concentrations. Summer stratification length was 2 days shorter and 7% less stable with the intervention. Our results suggest that the change to water residence time in Elterwater was insufficient to induce large enough physical changes to improve water quality. However, the minor physical changes suggest the management measure had some impact and that larger changes in water residence time may have the potential to induce reductions in internal loading. Future assessments of management requirements should combine multi-year observations and physical lake modelling to provide improved understanding of the intervention effect size required to alter the physical structure of the lake, leading to increased hypolimnetic oxygen and reduced potential for internal loading. Graphical abstract: Image 1 Highlights: Novel restoration efforts require robust impact assessments to determine success. Reducing water residence time caused minors effects on lake temperature. Changes to residence time were insufficient to significantly improve water quality. Modelling and long-term field data give valuable insights into restoration impacts.